Explanation:
The given reaction equation will be as follows.
[tex][FeSCN^{2+}] \rightleftharpoons [Fe^{3+}] + [SCN^{-}][/tex]
Let is assume that at equilibrium the concentrations of given species are as follows.
[tex][Fe^{3+}] = 8.17 \times 10^{-3}[/tex] M
[tex][SCN^{-}] = 8.60 \times 10^{-3}[/tex] M
[tex][FeSCN^{2+}] = 6.25 \times 10^{-2}[/tex] M
Now, first calculate the value of [tex]K_{eq}[/tex] as follows.
[tex]K_{eq} = \frac{[Fe^{3+}][SCN^{-}]}{[FeSCN^{2+}]}[/tex]
= [tex]\frac{8.17 \times 10^{-3} \times 8.60 \times 10^{-3}}{6.25 \times 10^{-2}}[/tex]
= [tex]11.24 \times 10^{-4}[/tex]
Now, according to the concentration values at the re-established equilibrium the value for [tex][FeSCN^{2+}][/tex] will be calculated as follows.
[tex]K_{eq} = \frac{[Fe^{3+}][SCN^{-}]}{[FeSCN^{2+}]}[/tex]
[tex]11.24 \times 10^{-4} = \frac{8.12 \times 10^{-3} \times 7.84 \times 10^{-3}}{[FeSCN^{2+}]}[/tex]
[tex][FeSCN^{2+}] = 5.66 \times 10^{-2}[/tex] M
Thus, we can conclude that the concentration of [tex][FeSCN^{2+}][/tex] in the new equilibrium mixture is [tex]5.66 \times 10^{-2}[/tex] M.